The Effect of Passive Smoking on Mucociliary Clearance and Inferior Concha Reactivity - OYSU, ÇAĞATAY (SAGE PUBLICATIONS INC, 2021)
Introduction The aim of this study is to investigate the effect of cigarette smoke on turbinate reactivity and mucociliary clearance (MCC) in passive smokers. Methods 60 adult patients (30 passive smokers and 30 healthy subjects as the control group) were recruited for this study. Following a questionnaire on passive smoke exposure, MCC measurement using the saccharin test was carried out to all participants. The baseline and after decongestant acoustic rhinometry values (MCA1, MCA2, VOL1, VOL2) were measured and the percentage changes between the two test values (ie; response to nasal decongestants = concha reactivity) were recorded. Results All 60 patients, including 37 women (61.7%) and 23 men (38.3%) were between 18-57 years of age . MCC's average measurements were 11.13 minutes in the passive smokers group, 7.87 minutes in the control group, which was statistically significantly different (p < 0.05). There was a statistically significant difference between the passive smokers and control group for acoustic rhinometric measurement of the ratio of MCA2 and VOL2 values before and after decongestant application (p < 0.05). Discussion Passive smoking can damage the nasal mucosa at least as active smoking. The number of studies on this subject is limited. There are no studies in the literature showing the effect of cigarette smoke on the inferior turbinate mucosal response. In our study, the inferior turbinate decongestant capacity was found to be significantly decreased in the passive smokers compared to the control group. Conclusion As a result of cigarette exposure, the erectile function of the lower turbines may be impaired. The task of the ENT physicians is to warn the passive smokers in this regard.
Keywords: passive smoking; mucociliary clearance; acoustic rhinometry; saccharin test